Classifying insulin regimens – difficulties and proposal for comprehensive new definitions. Issue 6 (10th April 2015) - Neu, A; Lange, K; Barrett, T; Cameron, F; Dorchy, H; Hoey, H; Jarosz‐Chobot, P; Mortensen, HB; Robert, J‐J; Robertson, K; de Beaufort, C; on behalf of the Hvidoere Study Group
<x xml:space="preserve">Abstract</x> Modern insulin regimens for the treatment of type 1 diabetes are highly individualized. The concept of an individually tailored medicine accounts for a broad variety of different insulin regimens applied. Despite clear recommendations for insulin management in children and adolescents with type 1 diabetes there is little distinctiveness about concepts and the nomenclature is confusing. Even among experts similar terms are used for different strategies. The aim of our review – based on the experiences of the Hvidoere Study Group (HSG) – is to propose comprehensive definitions for current insulin regimens reflecting current diabetes management in childhood and adolescence. The HSG – founded in 1994 – is an international group representing 24 highly experienced pediatric diabetes centers, from Europe, Japan, North America and Australia. Different benchmarking studies of the HSG revealed a broad variety of insulin regimens applied in each center, respectively. Furthermore, the understanding of insulin regimens has been persistently different between the centers since more than 20 yr. Not even the terms 'conventional' and 'intensified therapy' were used consistently among all members. Besides the concepts 'conventional' and 'intensified', several other terms for the characterization of insulin regimens are in use: Basal Bolus Concept (BBC), multiple daily injections (MDI), and flexible insulin therapy (FIT) are most frequently used, although none of these expressions is clearly or consistently defined. The proposed new classification for insulin management will be comprehensive, simple, and catchy. Currently available terms were included. This classification may offer the opportunity to compare therapeutic strategies without the currently existing confusion on the insulin regimen.